Effect of PIN Diode Integration on Patch Antennas for Frequency Reconfigurable Antenna Applications - Boyapati Bharathidevi; Jayendra Kumar (Advances in Technology Innovation, 2023)
PIN diodes are commonly used to design reconfigurable antennas owing to their sufficient isolation, lower cost, and ease of fabrication. This study aims to explore the effect of biasing conditions of a PIN diode radio frequency (RF) switch on a frequency-reconfigurable antenna. This approach investigates the contribution of the forward diode current and the reversed biased voltage on the shift in the operating band, the impedance matching, and the radiation efficiency of a reconfigurable antenna. The benefits and drawbacks of different approaches to modeling PIN diode RF switches are demonstrated on Ansys electromagnetic switch. The result shows a significant match between simulated and measured operating bands, impedance matching, and radiation efficiency. The proposed RF switch model can be used as a practical simulation model for implementing various reconfigurable microwave components.